Peningkatan Partisipasi Belajar Siswa Kelas VI Pada Pembelajaran PKn Dengan Menggunakan Model Guided Teaching Di SDN 17 Batang Anai Kabupaten Padang Pariaman - Eva Wardanis (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
This research is based on the lack of student’s participation in learning PKn subject. This research is aimed to improve the participation in learning of students grade VI SDN 17 Batang Anai by implementing guided teaching model. This is a class action research that consists of two cycles including four steps: planning, action, observation, and reflection. Data of research were obtained through observation sheets, and test. Obtained data were analyzed quantitatively and qualitatively. Percentage of student’s participation in proposing ideas is 30% in cycle I and become 77.5% in cycle II. Meanwhile, percentage of student’s participation in answering questions is 40% in cycle I and become 85% in cycle II. Percentage of student’s participation in proposing questions is 17.5% in cycle I and become 70% in cycle II. Hence, it can be concluded that guided teaching model can improve participation in learning PKn subject of students grade VI SDN 17 Batang Anai Kabupaten Padang Pariaman.